1998
DOI: 10.1002/jlb.63.3.331
|View full text |Cite
|
Sign up to set email alerts
|

Identification of glyceraldehyde-3-phosphate dehydrogenase as a Ca2+-dependent fusogen in human neutrophil cytosol

Abstract: The membrane fusion events observed during neutrophil degranulation are important aspects of the immunoregulatory system. In an attempt to understand the regulation of granuleplasma membrane fusion, we have begun characterizing human neutrophil cytosol for fusion activity, finding that 50% of the fusogenic activity could be attributed to members of the annexin family of proteins. The major non-annexin fusion activity (25% of the total cytosolic activity) was enriched by ion exchange chromatography after deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…Lastly, it has been reported that GAPDH undergoes autophosphorylation as well as phosphatidylserine (PS)-dependent phosphorylation by PKC (18 -20). Although GAPDH is commonly known as a key enzyme in glycolysis (GAPDH catalyzes the NAD-mediated oxidative phosphorylation of glyceraldehyde 3-phosphate to 1,3-diphosphoglycerate), a number of intriguing intracellular roles have been reported including modulation of the cytoskeleton, kinase activity, and the promotion of vesicle fusion (18,(21)(22)(23)(24). These activities are all essential to the maintenance of mem-brane trafficking.…”
mentioning
confidence: 99%
“…Lastly, it has been reported that GAPDH undergoes autophosphorylation as well as phosphatidylserine (PS)-dependent phosphorylation by PKC (18 -20). Although GAPDH is commonly known as a key enzyme in glycolysis (GAPDH catalyzes the NAD-mediated oxidative phosphorylation of glyceraldehyde 3-phosphate to 1,3-diphosphoglycerate), a number of intriguing intracellular roles have been reported including modulation of the cytoskeleton, kinase activity, and the promotion of vesicle fusion (18,(21)(22)(23)(24). These activities are all essential to the maintenance of mem-brane trafficking.…”
mentioning
confidence: 99%
“…49 A growing amount of evidence has shown that the glycolytic enzymes GAPDH and enolase also play a role in membrane fusion. [52][53][54][55][56] The capacity of NO and agents that disrupt the actin cytoskeleton to induce TVE formation could be realized via the L-plastin is a single cytosolic protein in neutrophils that binds BPB, an inducer of TVE formation. 74 In murine macrophages, L-plastin is one of the major S-nitrosylation targets for NO, a natural inducer of TVE formation.…”
Section: -364mentioning
confidence: 99%
“…84 Annexin 1 and GAPDH appear to be the major fusion proteins of neutrophils shown to promote aggregation and fusion neutrophil granules. 53,85,86 The S100A8/A9 protein binds and transports arachidonic acid, 87 an essential component of annexin-mediated membrane fusion.…”
Section: The Role Of Actin Cytoskeleton In Tve Formation In Neutrophimentioning
confidence: 99%
“…It is known that GAPDH can cause the fusion of reconstituted phospholipid vesicles in vitro (49). We recently reported that rabbit GAPDH binds to phosphatidylserine in lipid bilayers and stimulates membrane fusion of reconstituted phospholipid vesicles (28).…”
Section: Analysis Of Proteins Participating In Nuclear Assembly Bymentioning
confidence: 99%